The handbook of logistics & distribution management - Rushton, Alan; Croucher, Phil, 1954-; Baker, Peter, 1950- (Kogan Page, 2010)
Explains the nuts and bolts of logistics and distribution. Covering the major elements of modern logistics, this guide includes chapters on: supply chain segmentation, air transport, maritime transport, outsourcing services and decision making and outsourcing management. It provides an explanation of the various technologies. Newly updated, it includes revisions to essential areas such as manufacturing logistics, integrated logistics, process design and home delivery.
Keywords: Physical distribution of goods -- Management -- Handbooks, manuals, etc.; elektronické knihy; electronic books